Kemampuan Pedagogical Content Knowledge (PCK) Mahasiswa Pendidikan Biologi FKIP UMS Dalam Menyusun RPP Kurikulum 2013 Tahun Akademik 2016/2017 - SUKMA HAPSARI, INGGRID; , Dra. Hariyatmi, M.Si (2017)
A dedicated professional teacher should has ability and skills in term of teaching. Professional teacher competences derived as three pillars knowledge which are content knowledge/CK, pedagogical knowledge and specific intersection field between CK and PK namely Pedagogical Content Knowledge (PCK). The significance of this research is to find out PCK competence of biology students of Faculty of Teachers Training and Education Muhammadiyah University of Surakarta in the Preparation of Lesson Plan Curriculum 2013 in Academic Year 2016/2017. This research use descriptive with strategy of case studies. The used methods in this research is documentation in order to obtain data CK, PK and PCK. The population in this research is the biology students faculty of Teachers Training and Education Muhammadiyah University of Surakarta batch 2014 which passed subject: Teaching Biology Planning. The result of this research shows that PCK competences of students has a percentage 71.18%. Therefore, it can be conclude that PCK competence of biology students of Faculty of Teachers Training and Education Muhammadiyah University of Surakarta is good.